The Effects of a Brief Meditative Breathing Session on Recovery from Moderate Aerobic Exercise - Emery, Anna; Lucas, Tosha; Miller, Adam; Reeves, Isaiah; Ward, Amanda (Journal of Advanced Student Sciences (JASS), 2016)
Meditative practices have been shown to have many beneficial effects such as performance boosts, relaxation, and reductions in anxiety. Studies among athletes have shown a correlation between enhanced physical ability and meditative practice. While previous studies have examined effects of long-term meditative improvements, we examined how a single meditative breathing session affected recovery rates. Our study investigated if a positive correlation exists between acute meditative breathing prior to exercise and recovery time. Our study examined three physiological variables: heart rate, respiratory rate, and grip strength. Heart rate and respiratory rate recovery were measured over time, while grip strength was compared to original baselines for a percent change for control and experimental groups. The effects of meditation on recovery time were not statistically significant and therefore did not support our hypothesis. A single acute meditative breathing session prior to exercise did not have any effect on recovery rate after exercise. Different modifications in future studies may show a significant difference between these variables and more fully explain the effects of mediation on aerobic recovery time.
An article that appeared in JASS, issue 2016
Keywords: aerobic; cardiovascular; exercise; fatigue; meditation; muscle; performance; relaxation; respiration; strength; sympathetic nervous system